Analyzing the Muddles of Analysis: (Some of) What Analytic Theologians Can Learn from the History of Analytic Feminism. (6th May 2019) - Rutledge, Jonathan C.
Abstract: Analytic theologians have ironically experienced difficulties in precisely defining the meaning of 'analytic' with respect to their style of theology. In this article, I turn to the history of a similar research project, analytic feminism, to see how it went about defining 'analytic' in relation to the typically non‐analytic subject area of feminist studies. I then consider two commonly referred to attempts to define analytic theology, one methodological and the other socio‐historical, and discuss shortcomings of each. I close with a new definition of analytic theology that aims to incorporate all the insights in the discussions which precede it.